Engineering the Erythromycin-Producing Strain Saccharopolyspora erythraea HOE107 for the Heterologous Production of Polyketide Antibiotics - Lü, Jin; Long, Qingshan; Zhao, Zhilong; Chen, Lu; He, Weijun; Hong, Jiali; Liu, Kai; Wang, Yemin; Pang, Xiuhua; Deng, Zixin; Tao, Meifeng (Frontiers in Microbiology, 2020)
Bacteria of the genus Saccharopolyspora produce important polyketide antibiotics, including erythromycin A (Sac. erythraea) and spinosad (Sac. spinosa). We herein report the development of an early industrial erythromycin-producing strain, Sac. erythraea HOE107, into a host for the heterologous expression of polyketide biosynthetic gene clusters (BGCs) from other Saccharopolyspora species and related actinomycetes. To facilitate the integration of natural product BGCs and auxiliary genes beneficial for the production of natural products, the erythromycin polyketide synthase (ery) genes were replaced with two bacterial attB genomic integration sites associated with bacteriophages phiC31 and phiBT1. We also established a highly efficient conjugation protocol for the introduction of large bacterial artificial chromosome (BAC) clones into Sac. erythraea strains. Based on this optimized protocol, an arrayed BAC library was effectively transferred into Sac. erythraea. The large spinosad gene cluster from Sac. spinosa and the actinorhodin gene cluster from Streptomyces coelicolor were successfully expressed in the ery deletion mutant. Deletion of the endogenous giant polyketide synthase genes pkeA1-pkeA4, the product of which is not known, and the flaviolin gene cluster (rpp) from the bacterium increased the heterologous production of spinosad and actinorhodin. Furthermore, integration of pJTU6728 carrying additional beneficial genes dramatically improved the yield of actinorhodin in the engineered Sac. erythraea strains. Our study demonstrated that the engineered Sac. erythraea strains SLQ185, LJ161, and LJ162 are good hosts for the expression of heterologous antibiotics and should aid in expression-based genome-mining approaches for the discovery of new and cryptic antibiotics from Streptomyces and rare actinomycetes.